2022
DOI: 10.3390/jcdd9010029
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Maternal Point of Care Ultrasound on Labor and Delivery Wards

Abstract: Point-of-care ultrasonography (POCUS) refers to limited bedside ultrasound used to evaluate patients for conditions specific to the scope of their practice. Given the benefits of its application, interest in its use is increasing. We aimed to review the literature and assess the potential feasibility of using POCUS of the heart and lungs in the field of obstetrics. We aim to describe its relevance and value as an adjunctive tool for critically ill obstetric patients on labor and delivery wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…These include situations involving maternal abdominal hemorrhage in the case of uterine rupture. 2 Furthermore, research has shown that transabdominal sonography can play a crucial role in revealing retroplacental hemorrhage, even in the absence of vaginal bleeding, but when accompanied by fetal bradycardia. This allows physicians to make urgent decisions, such as the option to terminate pregnancy, performing C section, to reduce the risk of intrauterine fetal death or hypoxic brain injury resulting from delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include situations involving maternal abdominal hemorrhage in the case of uterine rupture. 2 Furthermore, research has shown that transabdominal sonography can play a crucial role in revealing retroplacental hemorrhage, even in the absence of vaginal bleeding, but when accompanied by fetal bradycardia. This allows physicians to make urgent decisions, such as the option to terminate pregnancy, performing C section, to reduce the risk of intrauterine fetal death or hypoxic brain injury resulting from delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ultrasonography has become one of the most widely accepted devices by health care professionals in the field of critical care. 1,2 The utility of this method also extends to patients admitted to the intensive care unit (ICU) due to obstetric pathologies, 3 allowing for the diagnosis of pregnancy during focused assessment with sonography in trauma and the assessment of fetal vitality and viability. 4,5 Point-of-care ultrasonography (POCUS) is a real-time bedside sonographic evaluation used to quickly diagnose and treat patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Portable ultrasound machines are now almost ubiquitous in emergency departments. Clinicians increasingly use ultrasound for focused purposes such as peripheral arterial or venous access, central venous catheter insertion, focused assessment with sonography for trauma (FAST) scanning for intra-abdominal hemorrhage, and obstetric fetal assessment [5][6][7]. To date, uptake by surgeons in diagnosing other abdominal emergencies has been limited [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, echocardiography, even in low-risk individuals and especially in those who have hypertension or obesity, may reveal abnormal findings which could be important in risk stratification or treatment [ 7 ]. Lastly, a point-of-care ultrasound of the heart and lungs on the Labor and Delivery ward affords the quicker triaging of cardiac versus non-cardiac diagnoses, such as acute congestive heart failure [ 8 ].…”
mentioning
confidence: 99%